2021
DOI: 10.1017/jfm.2021.832
|View full text |Cite
|
Sign up to set email alerts
|

Bistabilities in two parallel Kármán wakes

Abstract: Bistabilities of two equilibrium states discovered in the coupled side-by-side Kármán wakes are investigated through Floquet analysis and direct numerical simulation (DNS) with different initial conditions over a range of gap-to-diameter ratio ( $g^*= 0.2\text {--}3.5$ ) and Reynolds number ( $Re = 47\text {--}100$ ). Two bistabilities are found in the transitional $g^*-Re$ regions from in-phase (IP) to anti-phase (AP) vortex shedd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…In addition, one may find multiple attractors, which is associated to hysteresis, and it seems to be a common feature of many supercritical and subcritical flows, cf. (Subramanian, Sujith & Wahi 2013;Guo et al 2018;Ren et al 2021;Huang et al 2018;Suckale et al 2018). Eventually, for sufficiently large Reynolds numbers, Lorite-Díez & Jiménez-González (2020) and Pier (2013) identified irregular regimes for most rotation rates, which are associated to a T 3 -quasiperiodic attractor.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, one may find multiple attractors, which is associated to hysteresis, and it seems to be a common feature of many supercritical and subcritical flows, cf. (Subramanian, Sujith & Wahi 2013;Guo et al 2018;Ren et al 2021;Huang et al 2018;Suckale et al 2018). Eventually, for sufficiently large Reynolds numbers, Lorite-Díez & Jiménez-González (2020) and Pier (2013) identified irregular regimes for most rotation rates, which are associated to a T 3 -quasiperiodic attractor.…”
Section: Discussionmentioning
confidence: 98%
“…It was found that the flow at low Re undergoes transitions from a single bluff-body wake, via a flip-flop (FF) wake, to coupled-individual wakes such as in-phase (IP) and anti-phase (AP) flows with increasing g * . Other flow modes such as asymmetric single bluff-body vortex shedding flows and bistable flows are also found over the above parameter space (Ren et al 2021a). It is noteworthy that most of those studies are limited to low Re, where the flow was assumed to be two dimensional.…”
Section: Introductionmentioning
confidence: 93%
“…Floquet analysis is employed over one T due to the periodicity of the base flow. The selections of N t,s = 32 and K n = 16 were referred to the validation given by Carmo et al (2008) and Ren et al (2021a).…”
Section: Floquet Stability Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Flow past multiple bodies in close configuration is relevant for a range of applications, such as buildings or chimneys in urban and industrial environments, power lines, offshore structures, and heat exchangers. Even at relatively low Reynolds numbers, such flows can exhibit substantially more complexity than flow over a single, isolated body [33][34][35].…”
Section: Introductionmentioning
confidence: 99%